Psychological research : innovative methods and strategies - Haworth, John Trevor (Routledge, 1996)
Starting a research project, however large or small can be a daunting prospect. New researchers can be confronted with a huge number of options not only of topic, but of conceptual underpinning. It is quite possible to conduct research into say, memory, from a number of research traditions. Psychology also has links with several other disciplines and it is possible to utilise their techniques; the difficulty is quite simply the wide variety of methodological approaches that psychological research embraces. In this collection, authors have been recruited to explain a wide range of different.